A pilot-data based channel estimation method for OFDM relay-assisted systems - Neves, D.
In this work we propose and evaluate a pilot and data-based channel estimation scheme for SFBC OFDM-based cooperative scenario. We consider that both the base station and the relay node are equipped with double antenna arrays whereas the user terminal is a single antenna device. The relay protocol considered is equalise-andforward. In this paper we propose a channel estimation method that iteratively uses the information carried by the pilots and data to improve the estimate of the equivalent channels for the path Base Station – Relay Node – User Terminal. The MMSE criterion is used in the design of the estimator for both the pilot-based and data-aided iterations. The proposed method is evaluated in terms of the channel estimation MSE and the results show that the proposed scheme allows, with a single data iteration, a reduction of the number of pilots by a factor of approximately two when compared with non-data-aided schemes.